Fructose induces metabolic reprogramming in liver cancer cells, promoting aggressiveness and chemotherapy resistance - Lisette Chávez-Rodríguez; Alejandro Escobedo-Calvario; Verena Jendrossek; Johann Matschke; Maike Busch; Nicole Dünker; Moisés Vergara-Mendoza; Verónica Souza-Arroyo; Leticia Bucio-Ortiz; Roxana U. Miranda-Labra; Araceli Páez-Arenas; María Concepción Gutiérrez-Ruiz; et al. (Exploration of Digestive Diseases)
Aim: Fructose is a highly lipogenic compound related to the onset of steatosis, its progression to steatohepatitis, and the eventual initiation of hepatocellular carcinoma (HCC). One of the cancer hallmarks is the metabolic adaptation to the environmental sources; however, this characteristic could be exploited to manipulate the HCC tumor’s response to therapies. Due to the high prevalence in the consumption of diets enriched with fructose and the unclear results in the literature, it is pertinent to characterize the effects of fructose on the biology of HCC as a possible beneficial player in the aggressiveness of this cancer. We focused on investigating the metabolic effect of fructose on the aggressiveness of liver cancer cells and chemotherapy response. Methods: We treated Huh-7 and HepG2 liver cancer cell lines with 1 mM fructose to address the metabolic reprogramming and its fructose-induced effects. Results: Cancer cells use fructose as an alternative fuel source in glucose-starved conditions, ensuring tumorigenic properties and cell survival in both cell lines. The metabolic effect differed depending on cell line origin and aggressiveness. Conclusions: HCC cells showed a metabolic adaptation under fructose treatment, enhancing the pentose phosphate pathway to fuel anabolism. Metabolic rewiring also improves the tumorigenic properties and chemoresistance of cancer cells in vitro and in vivo, contributing to chemotherapy failure and the aggressiveness of liver cancer cells.